POLIO: OBSTACLES TO ERADICATION - А. Ю. Фесенко; В. К. Позур (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2013)
Review is devoted to the situation of poliomyelitis in Ukraine and worldwide. For many years, the problem of polio remains relevant. Today circulation of «wild» strains of poliovirus continues in the three endemic countries in Asia and Africa. Thanks to the continuous growth of migration threatens to deliver «wild» polioviruses to the countries, free from virus circulation. It was demonstrated the low level of vaccination coverage of children in Ukraine, that leads to increased segment of the population susceptible to the disease. It was demonstrated the increase in the incidence of vaccine-associated paralytic poliomyelitis mainly in developed countries, due to the strengthening of epidemiological surveillance of poliomyelitis on the one hand, and the increasing number of persons with immunodeficiency states – on the other. It was reproduced the mechanism of viral revertants with the possible return of their entry neurovirulence properties and formation of virus interspecies recombinants. The review shows the main objectives of WHO, to combat polio, which ultimate goal is the complete eradication of the disease.